ANALISIS PERFORMANSI PROTOKOL SIP UNTUK SIGNALLING VOIP MENGGUNAKAN RSVP PADA NEXT GENERATION NETWORK - Adhi Prakosa, Bayu (Krea-TIF: Jurnal Teknik Informatika, 2015)
Next Generation Network (NGN) designed to fulfill requirement of Infrastructure Information Communication in past Century 21. Network is expected shall nolonger have the character of TDM but have in the form ofefficient packages, but with (QoS) guaranteed. (NGN) have tocan manage and bring is assorted traffic according torequirement of customer which continuously growth. ITU-TRec.Y.20001 (12/2004). VoIP defining a system using Internet Protocol Network for sending package voice out of one place to other place by usingbased IP Protocol. This Technology apply package process switchthat is process of delivery of data is assorted to become somesmalls parts for then sent through Networks based IP. SupportedProtocol VoIP also have progressively grow like SIP (SessionInitiation Protocol) which will do process connect and disconnecta call. To guarantee Quality of Service from Network generallyapply protocol (RSVP) Resource Reservation Protocol fordelivery of data.From result of this research was gotten by several conclusionsthat by using the mechanism without RSVP in VoIP Technologyin the NGN system Got results of the achievement of the systemthat was better for the number of user up to 200 users whereasthe number of users more than 200 achievement signalingfantastic used the RSVP scheme gave results of the achievementthat descended the existence of the increase in the number routerin the network core MPLS was seen by the existence of thedecline in the achievement of the system in the scheme no-RSVPwhereas the used codec will be influential againstjitter,latency,throughput and packet loss good in the RSVP andno-RSVP scheme also.